THE EFFECT OF Sauropus androgynus EXTRACT AND LEMURU OIL ON FAT DEPOSITION AND FATTY ACID COMPOSITION OF MEAT IN BROILER CHICKENS - Santoso, U.; Kususiyah, K.; Fenita, Y. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The present study was conducted to evaluate the effect of Sauropus androgynus (katuk) leavesextract (SAE) and lemuru fish oil (LO) on fat deposition and fatty acid composition of meat in broilerchickens. One hundred and fifty six broiler chickens were distributed to 13 treatment groups with 3cages in each treatment group as replicate. Completely randomized design was used in this study. Thethirteen groups were subsequent of broiler chickens that were fed diet containing commercial feedsupplement as a control (P1), 10 g/kg SAE and 1% LO (P2); 10 g/kg SAE and 1% LO plus 60 mgvitamin E (P3), 10 g/kg SAE and 2% LO (P4), 10 g/kg SAE and 2% LO plus 60 mg vitamin E (P5), 10g/kg SAE and 3% LO (P6), 10 g/kg SAE and 3% LO plus 60 mg vitamin E (P7), 18 g/kg SAE and 1%LO (P8), 18 g/kg SAE and 1% LO plus 60 mg vitamin E (P9), 18 g/kg SAE and 2% LO (P10), were18 g/kg SAE and 2% LO plus 60 mg vitamin E (P11), 18 g/kg SAE and 3% LO (P12), and 18 g/kg SAEand 3% LO plus 60 mg vitamin E (P13). The data were analyzed by analysis of variance and if it weresignificant, it were then determined by Duncan's Multiple Range test. The present results showed thatsupplementation of SAE and LO significantly affected (P<0.05) fat deposition in abdomen and leg, butit had no effect on neck fat deposition and Fatty Liver Score. Supplementation of SAE and LO hadsignificantly reduced (P<0.05) cholesterol content and thiobarbituric acid (TBA) in leg meat, but itsignificantly increased (P<0.05) vitamin A and vitamin E and it had no effect on fat in leg meat.Supplementation of SAE and LO proved to change fatty acid composition in leg meat. The treatmenthighly significant increased ecosapentaenoic acid (EPA) and docosahexaenoic acid DHA (P<0.01),arachidonic acid and stearic acid (P<0.05), but it significantly reduced linolenic acid (P<0.05). Inconclusion, the supplementation of SAE and LO reduced fat deposition in abdomen and leg, the contentof cholesterol in meat, and it enriched EPA and DHA of meat.